CORRELATION OF INCREASING MATERNAL GRAVIDITY WITH SEVERITY OF POLYHYDRAMNIOS - Perveen, Saima; Haleemi, Surraya; Khattak, Saniya Tanveer (Journal of Postgraduate Medical Institute, 2013)
Objective: To find correlation of increasing maternal gravidity with severity of polyhydramnios. Methodology: This descriptive study was done in Gynecology & Obstetrics department, Khyber TeachingHospital, Peshawar, from July 2010 to December 2011. Patients were included in the study by consecutivenon-probability sampling after fulfilling the inclusion criterion and given informed written consent.Detailed history about the status of maternal gravidity was taken and thorough per abdominal and vaginalexaminations were performed. Polyhydramnios was confirmed ultrasonographically and categorized asmild, moderate or severe on the basis of amniotic fluid index. SPSS 16 was used for analyzing thedescriptive data. Spearman rank correlation analysis (í£) was used to measure the strength of associationbetween pairs of variables. Results: The total number of patients were 532. Mean age was 30.30±6.28years and mean age ofgestational amenorrhea was 35.6±3.35weeks (28-41). The maximum number of patients (57.4%) were inthe age range group of 23-30 years. The number of patients with primary gravida were 33.6%(n=180),38.8%(n=206) were with multigravida and 27.6%(n=146) with grand multigravida. Severe polyhydramnioswas in 10.4%(n=55) cases while moderate and mild in 25.5%(n=135) and 64.1%(n=341) respectively.Majority of the patients having mild polyhydramnios were primary gravida or multigravida while thegrandmultigravida patients were mostly either having moderate or severe polyhydramnios. The spearmanrank correlation coefficient between the pairs of variables was (í£) + 0.02, (p=0.04). Conclusion: Increasing maternal gravidity has weak positive correlation with severity of polyhydramnios.